FISCAL POLICY AND SMALL AND MEDIUM SCALE ENTERPRISES PERFORMANCE IN NIGERIA - Ebenezer, Ariyibi Mayowa; O, Efemena Emily; Enitan, Olowofela Olusola (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The macroeconomic policies, which fiscal policy is inclusive of, are very germane in determining the performance level in the country, most especially in determining the developmental quota that the small and medium scale enterprises would contribute to the economy, so poor usage of the fiscal policy can stifle the effectiveness of the SMEs’ performance, and their contributive role has a source of growth in an economy. Based on their relevance, this study examines the impact of fiscal policy on small and medium-scale enterprises' performance in Nigeria. The secondary time series data was sourced from the Central Bank Statistical Bulletin and the National Bureau of Statistics from the period 1991 to 2022. The ARDL (Auto-Regressive Distributed Lag) was employed to draw inferences after being informed by the unit-root test. The findings revealed that the expansionary measure of fiscal policy shows that government re-recurrent expenditure has a negative insignificant effect on small and medium-scale enterprises' total credit from commercial banks. Government capital expenditure has a negative significant effect on small and medium-scale enterprises' total credit from commercial banks. The contractionary measure of fiscal policy shows that value-added tax has a positive significant effect on small and medium-scale enterprises' total credit from commercial banks. Company income tax has a negative significant effect on small and medium-scale enterprises' total credit from commercial banks, while electricity consumption has a negative insignificant effect on small and medium-scale enterprises' total credit from commercial l banks. It is therefore recommended that policymakers should enhance the efficiency of capital expenditure to support SME-enabling projects and infrastructure. Keywords: Fiscal Policy; SME’s; Government Expenditure; Taxation and ARDL